Громадська діяльність Тита Войнаровського - Шевченко, О.В. (Український історичний журнал, 2008)
Отець-мітрат Тит Євген Войнаровський-Столобут - церковний та громадсько-політичний діяч кінця XIX - першої половини ХХ ст. - заслуговує на увагу передусім як непересічна особистість, яка намагалася підняти рівень освіти селянства та поліпшити його економічне становище. Як священик та громадський діяч він репрезентує греко-католицьке духівництво свого часу. The mitred father Tyt Yevhen Voynarovsky-Stolobut, the Halychyna priest. lived at the end of the XIX – the beginning of the XX century. Among other representatives of the priesthood he had been characterized by the extreme liking of a hard work and the real efficiency. Father Tyt spared no efforts in raising of the level of spirituality of his parishioners, and at the same time, he paid a lot of attention to the development of education in the country and to the improvement of the economic conditions of the peasantry of Halychyna.